Transformasi Pemasaran Digital : Sebagai Strategi Daya Saing UMKM di Era Digital - Rexy Andalangi Maatuil; Reine Salunusa; Keisya Manarat; Nadia Bartei; Chelsy Yahya; Josua Mewo (Indo Publishing, 2025)
This study examines the transformation of digital marketing as a strategic effort to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Using a qualitative case study approach, the research explores how five MSMEs in Manado adopt digital platforms primarily Facebook and WhatsApp to promote their products, engage customers, and expand market reach. Findings reveal that digital marketing provides significant benefits, including increased sales, broader audience coverage, and improved customer retention. However, MSMEs still face several challenges, such as limited digital competencies, unstable internet connectivity, fluctuating consumer demand, and growing online competition. Most marketing strategies remain basic, dominated by photo postings without advanced content creation. Social and familial support plays an important role in assisting MSMEs in managing digital platforms. The study also highlights the strong expectation for government support, particularly in the form of digital marketing training and capacity-building programs. Overall, digital marketing has become a vital instrument for MSME sustainability, although its utilization requires further optimization to achieve long-term competitiveness.